One Method of Classification of Urbanonyms as a Historical Source - Долинська, Мар'яна (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
In their studies on the classification of the toponyms historians mainly use the methods of linguistics. These methods of classification are not appropriate for the urbanonyms because it is impossible to fit urbanonyms in with the hierarchical structure of the topononyms.  Each town is a complex spatial, social and cultural formation (object). This complexness influenced the creation of the proper names. Therefore, a classification of denotats (objects) rather than the classification of their names is suggested. In such context one can see the objects themselves as real formations in town’s space and their proper names reflecting the conception of this space.